Report on currency and finance 1988-89 : vol II : statistical statements - Reserve Bank of India ([Bombay] : Reserve Bank of India, 1989)
This volume contains information on the statistical analysis for the year (April and March)
Volume II
usc 10/04/2019
Ref.
Keywords: Banks and banking, Central; Finance; Currency question; Public finance; Economic conditions; India